Teleworking, unpaid work and gender violence in Ecuador during the COVID-19 pandemic - Peña-Contreras, Eva-Karina; Calderón-López, María-del-Carmen; Arias-Medina, Paúl; Sacaquirin Rivadeneira, Cristina (Maskana, 2021)
The objective of this research was to explore the difficulties around telework, unpaid work and gender violence in Ecuador from a gender perspective. The sample consisted of voluntary participants (men and women). It was obtained through an invitation on the Facebook social network and through agreements with public and private companies, in which people were teleworking (n = 533). The findings suggested that women have been the most affected during the COVID-19 pandemic by having to telecommute and at the same time performing care and household tasks (unpaid work). With this, the perception of an absence of co-responsibility in these tasks on the part of men has been visible. These inequalities show the presence of gender roles that determine the socially accepted and valued patterns of action, both for women and men. A clear example of this is machismo and Marianism, which continue to be the last in Latin American societies and which mark the basis of what should be expected of a feminized woman. Finally, regarding gender violence during the pandemic, our results showed that, in addition to not being statistically significant, it was a very small number of reported cases.